A magnetometer-based method for in-situ syncing of wearable inertial measurement units - Gilbert, Thomas J.; Lin, Zexiao; Day, Sally; Hamilton, Antonia F. de C.; Ward, Jamie A. (Frontiers in Computer Science, 2024)
This paper presents a novel method to synchronize multiple wireless inertial measurement unit sensors (IMU) using their onboard magnetometers. The basic method uses an external electromagnetic pulse to create a known event measured by the magnetometer of multiple IMUs and in turn uses this to synchronize the devices. An initial evaluation using four commercial IMUs reveals a maximum error of 40 ms per hour as limited by a 25 Hz sample rate. Building on this we introduce a novel method to improve synchronization beyond the limitations imposed by the sample rate and evaluate this in a further study using 8 IMUs. We show that a sequence of electromagnetic pulses, in total lasting <3-s, can reduce the maximum synchronization error to 8 ms (for 25 Hz sample rate, and accounting for the transient response time of the magnetic field generator). An advantage of this method is that it can be applied to several devices, either simultaneously or individually, without the need to remove them from the context in which they are being used. This makes the approach particularly suited to synchronizing multi-person on-body sensors while they are being worn.